‘Coming In’ as Indigenous, Queer, and Urban – Utilising Indigenous Queer Standpoint Theory as Methodology - Souksavanh T. Keovorabouth (Journal of Global Indigeneity)
This article outlines my positionality, a crucial aspect of Indigenous research, to explore two guiding questions: 1) How do Native American Queer, Trans, and Two-Spirit individuals experience settler-colonial urbanization? and 2) How do their resilience, resistance, agency, and self-determination reshape urban spaces for Native American communities in Phoenix, Arizona? Utilizing Indigenous Queer Standpoint Theory, I draw on theoretical insights from Torres Strait Islander scholar Martin Nakata (2008) Indigenous Standpoint Theory and the concept of “coming in” by Two-Spirit Cree scholar Alex Wilson (2015). This framework, informed by my Diné cultural practices, defines my standpoint, and examines the intersections of place and space in urban areas. My insider perspective, as a Queer, Trans, and urban Diné person, strengthens my connection to the participants and the community. The research underscores the complexities of multifaceted identities and the necessity for qualitative research to benefit the communities involved, aligning with Indigenous methodologies and self-determination principles.